Controlling root-knot nematode Meloidogyne incognita in tomatoes using modified effective microorganisms-fermented plant extract and compost manure - Benoit Sossou; Nkechi Izuogu; Aisha Anifowose; H. Ahamefule (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Nematode diseases are major constraints in tomato production. Screenhouse and field experiments were conducted to assess the efficacy of Effective Microorganisms-Fermented Plant Extract (EM-FPE) and compost manure singly and in combination on Meloidogyne incognita infecting tomatoes.Method Screenhouse and field experiments were designed respectively as 2×5 and 2×4 factorial fitted into a completely randomized design (CRD) in the screenhouse and randomized complete block design (RCBD) on the field. For single treatments, 100 ml of EM-FPE or 200 g of compost was used per plant while 50 ml of EM-FPE and 100 g of compost were combined and used per plant for treatment combination. Pots that did not receive any treatment served as control. Data were collected on growth parameters, fruit production, galling, and soil nematode population. The data collected was subjected to analysis of variance (ANOVA) where significant differences in means were separated using Fisher’s Least Significance Difference (LSD) Test at P = 0.05.Results In both trials, treated plants performed significantly better. No significant difference was recorded among the three treatments for soil nematode population and root galling on the field. But in the screenhouse trial, plants treated with the combination of EM-FPE and compost recorded higher soil nematode population (150) and root galling (7) at harvest but the plants performed well. Among the treatments, compost manure applied singly gave the best result with respect to vegetative growth, flower formation, and yield of the tomatoes.Conclusion This study reveals that both treatments, EM-FPE, and compost manure could be relied on for effective control of Meloidogyne incognita in tomatoes.